2007
DOI: 10.1111/j.1834-7819.2007.tb00511.x
|View full text |Cite
|
Sign up to set email alerts
|

An unusual maxillary first molar with four roots and six canals: a case report

Abstract: This case report presents an unusual maxillary right first molar with four roots and six canals. Endodontic treatment was provided and final restoration was accomplished with composite resin. Treating extra canals in maxillary first molars may be challenging. Inability to find and properly treat the root canals may cause failures. Complete clinical and radiographic examination and a thorough knowledge of the morphology of these teeth is necessary for successful clinical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…One study showed a C-shaped canal configuration 14 in the maxillary molar. These studies also reported variations in the number of canals per root [15][16][17] .…”
Section: Discussionmentioning
confidence: 90%
“…One study showed a C-shaped canal configuration 14 in the maxillary molar. These studies also reported variations in the number of canals per root [15][16][17] .…”
Section: Discussionmentioning
confidence: 90%
“…A thorough knowledge of root canal morphology and the configuration of the teeth plays an important role in the success of endodontic therapy (12). Several reports have described the presence of aberrant canals in the mandibular first molar that includes the presence of three canals in the mesial root (3)(4)(5)13).…”
Section: Discussionmentioning
confidence: 99%
“…[5] Many studies have reported the presence of abnormal canals in the mandibular first molar with other three canals in the mesial root as well as in the distal root. [6][7][8] Furthermore, there is one case report which is related to six canals (two mesial and four distal canals in two distal roots) in literature.…”
Section: Discussionmentioning
confidence: 99%